CROP DISEASES AND PESTS AND THEIR CONTROL MEASURES - Guljamol Raxmanjanovna Raxmonova; Qosimova Muharramxon Kodirjonovna (Web of Journals Publishing, 2024)
This article provides information about the importance of cereals in the national economy, beneficial properties, as well as biology, development and harm of harmful organisms.
Keywords: mosh, cultivation, technology, disease, pest, entomophage